2011
DOI: 10.1016/j.neuint.2011.03.022
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ inhibition enhances tyrosine hydroxylase phosphorylation in mice after methamphetamine treatment

Abstract: The present study was designed to evaluate the specific role of protein kinase C (PKC) δ in methamphetamine (MA)-induced dopaminergic toxicity. A multiple-dose administration regimen of MA significantly increases PKCδ expression, while rottlerin, a PKCδ inhibitor, significantly attenuates MA-induced hyperthermia and behavioural deficits. These behavioural effects were not significantly observed in PKCδ antisense oligonucleotide (ASO)-treated- or PKCδ knockout (−/−)-mice. There were no MA-induced significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 74 publications
0
38
0
Order By: Relevance
“…Consistent with these studies, we demonstrated in an in vivo study that administering rottlerin, a PKC␦-specific inhibitor, protected against MPTP-induced loss of tyrosine hydroxylase-positive neurons in the nigrostriatum and the depletion of striatal dopamine and its metabolites, as well as MPTP-induced locomotor deficits (16). In a methamphetamine-intoxicated animal model, PKC␦ deficiency and rottlerin effectively attenuated methamphetamine-induced dopaminergic damage and behavioral deficits, further supporting that PKC␦ could represent a valid pharmacological target for the treatment of dopaminergic neuronal degeneration (17,18). Interestingly, we also showed that PKC␦ negatively modulates dopamine synthesis by inhibiting the rate-limiting enzyme, tyrosine hydroxylase (3).…”
mentioning
confidence: 64%
“…Consistent with these studies, we demonstrated in an in vivo study that administering rottlerin, a PKC␦-specific inhibitor, protected against MPTP-induced loss of tyrosine hydroxylase-positive neurons in the nigrostriatum and the depletion of striatal dopamine and its metabolites, as well as MPTP-induced locomotor deficits (16). In a methamphetamine-intoxicated animal model, PKC␦ deficiency and rottlerin effectively attenuated methamphetamine-induced dopaminergic damage and behavioral deficits, further supporting that PKC␦ could represent a valid pharmacological target for the treatment of dopaminergic neuronal degeneration (17,18). Interestingly, we also showed that PKC␦ negatively modulates dopamine synthesis by inhibiting the rate-limiting enzyme, tyrosine hydroxylase (3).…”
mentioning
confidence: 64%
“…Likewise, protein kinase Cδ knock-out animals have reduced lipid peroxidation, protein oxidation, and behavioral deficits in response to methamphetamine. These studies were corroborated using pharmacological interventions, which also indicate increased tyrosine hydroxylase phosphorylation in response to methamphetamine (Shin et al, 2011, 2012). …”
Section: Partmentioning
confidence: 77%
“…Similarly, our recent report showed that PKCδ activation may be, at least in part, a factor in MA-induced hyperthermia [9]. However, pretreatment with reserpine, a drug known to produce hypothermia, does not prevent MA-induced neurotoxicity [95, 96].…”
Section: Discussionmentioning
confidence: 93%
“…The 4 × 7–10 mg/kg paradigm of methamphetamine (MA) administration in naïve animals is currently the most frequently used model that mimics acute toxic dosing of MA [1, 7-9]. This paradigm provides excellent relevance to intravenous and smoked routes of MA exposure in humans.…”
Section: Introductionmentioning
confidence: 99%